Stability and microbial community analysis during rotary drum composting of vegetable waste - V. Sudharsan Varma; Ajay S. Kalamdhad (International Journal of Recycling of Organic Waste in Agriculture)
Background Disposal of vegetable waste in landfills and illegal sites leads to emission of greenhouse gases and leachate production, thereby imposing major environmental issues. As an alternative, this waste can be successfully recycled for its high nutrient content using composting process. Results Five trials were made with the ratio of 6:3:1 of trial 1 (50 kg), trial 2 (70 kg), trial 3 (90 kg), trial 4 (120 kg) and trial 5 (150 kg) by adding 10 kg of dry leaves in each of the trials as bulking agent. Due to active microbial population and high biodegradable organic matter in vegetable waste, early thermophilic phase was observed within 18â24 h of the composting process in all of the trials with a maximum of 61.4 C in trial 3. Total mesophilic heterotrophs were observed in the range of 7.1 9 1011 CFU g-1 and gradually reduced to 2.65 9 106 CFU g-1 at the end of 20 days, which was considered due to prolonged thermophilic phase maintained in trial 3. An average of 54â56 C temperature was maintained for 7 days in trial 3, with spore-forming population in the order of 3.82 9 109 CFU g-1 contributing to higher organic destruction. The populations of fungus, actinomycetes and streptomycetes were observed to reduce during thermophilic phase and remained in the order of 2.85 9 104 , 3.8 9 106 and 4.1 9 105 CFU g-1 , respectively, at the end of 20 days. CO2 evolution and OUR were in the order of 0.89 and 0.32 mg g-1 VS d-1 , respectively, in trial 3 denoting maximum degradation of organic matter and stabilization of compost. Indicator organisms were found well with the standard limits due to elevated temperature. Conclusions Combinations of waste materials played a major role in favoring microbial succession. Temperature in the compost system had major effect on the survival of the microbial populations. Elevated temperatures favored higher degradation of organic matter, thereby stabilizing the compost within proposed time of composting and also destructing the indicator pathogens.